2022
DOI: 10.3390/bios12030178
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Novel Biosensor for Salivary Conductivity in Detecting Chronic Kidney Disease

Abstract: The prevalence of chronic kidney disease (CKD) is increasing, and it brings an enormous healthcare burden. The traditional measurement of kidney function needs invasive blood tests, which hinders the early detection and causes low awareness of CKD. We recently designed a device with miniaturized coplanar biosensing probes for measuring salivary conductivity at an extremely low volume (50 μL). Our preliminary data discovered that the salivary conductivity was significantly higher in the CKD patients. This cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 48 publications
2
9
0
Order By: Relevance
“…As a result, conductivity increases with frequency. The obtained values of conductivity at higher frequencies fully correspond to the values of salivary conductivity given in the literature, where lower values of conductivity can be considered values of 4.84 ± 1.01 μS/cm and higher values of 7.994 ± 1.02 μS/cm [ 26 ]. The value of conductance can be obtained by applying the following equations: G refers to the experimental conductance value, and R is defined as resistance.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…As a result, conductivity increases with frequency. The obtained values of conductivity at higher frequencies fully correspond to the values of salivary conductivity given in the literature, where lower values of conductivity can be considered values of 4.84 ± 1.01 μS/cm and higher values of 7.994 ± 1.02 μS/cm [ 26 ]. The value of conductance can be obtained by applying the following equations: G refers to the experimental conductance value, and R is defined as resistance.…”
Section: Resultssupporting
confidence: 80%
“…In this series of research, it has been demonstrated that in dehydrated healthy adults, an increase in salivary conductivity was linked to an increase in serum and urinary osmolality. Furthermore, it has also been found that salivary conductivity and age had strong correlations [ 26 ]. In this case, reduced saliva secretion due to xerostomia or dry mouth syndrome will influence the saliva’s compositions and conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature compensation through the MCU system allows the measurement signal to be obtained at 25 • C, and the result can be displayed on the OLED within 10 s (Figure 1D). Our device is highly reusable, as supported by previous research [29].…”
Section: The Sensing Devicesupporting
confidence: 63%
“…The portable device is easy-to-use and does not require specialized personnel to operate. Our initial data suggests a positive correlation between higher salivary conductivity and elevated fasting glucose levels, as well as an increased risk of developing chronic kidney disease [27][28][29]. However, further research is necessary to validate salivary conductivity as a reliable biomarker for diabetes.…”
Section: Introductionmentioning
confidence: 86%
“…The interference effects of BSA, urea, INS and SAA, which are some biological substances in saliva that may interfere with the PS/rGO-MNP-PDA/Anti-CRP immunosensor response developed for CRP detection, were investigated. The reference ranges of BSA (0.72–2.45 mg/mL) and urea (39–66 mg/dL) in saliva were determined according to the literature [ 69 , 70 ]. It was reported in the literature that SAA concentrations are generally between 20 and 50 mg/L for humans [ 71 ].…”
Section: Resultsmentioning
confidence: 99%